2018
DOI: 10.1111/jdi.12976
|View full text |Cite
|
Sign up to set email alerts
|

Polygonatum sibiricum polysaccharide potentially attenuates diabetic retinal injury in a diabetic rat model

Abstract: Aims/Introduction To investigate the protective effect of Polygonatum sibiricum polysaccharide ( PSP ) on the retina in diabetic rats. Materials and Methods A total of 120 Sprague–Dawley rats were randomly divided into blank control, control model (meaning diabetes mellitus), and diabetes mellitus with PSP intervention of high, medium and low doses groups. The difference of retinal vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Similar to the results of the present study that indicated PSP's role in anti-inflammation, previous studies also found that PSP played anti-inflammatory roles via IL-1β, il-6 and TnF-α (11,14). PSP also delayed the progression of diabetic retinopathy and cataracts (15,16), further indicating its therapeutic potential in T2dM.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to the results of the present study that indicated PSP's role in anti-inflammation, previous studies also found that PSP played anti-inflammatory roles via IL-1β, il-6 and TnF-α (11,14). PSP also delayed the progression of diabetic retinopathy and cataracts (15,16), further indicating its therapeutic potential in T2dM.…”
Section: Discussionsupporting
confidence: 91%
“…it is reported that PSP could inhibit inflammation such as interleukin (IL)-1β, il-6 and tumor necrosis factor (TnF)-α expression in lipopolysaccharide-treatment raW264.7, ovariectomized rat, acute heart failure rats, suggest that PSP had anti-inflammation effect (12)(13)(14). Moreover, PSP alleviated hyperglycemia and reduced oxidative stress to delay the progression of diabetic retinopathy and cataracts (15,16). Therefore, more studies are needed to further confirm the role and mechanism of PSP in regulating diabetes, especially T2DM.…”
Section: Polygonatum Sibiricum Polysaccharide Alleviates Inflammatorymentioning
confidence: 99%
“…Carboxymethyl Terminalia catappa polysaccharides show therapeutic effects in the cornea from blue light-emitting diodes. Moreover, Polygonatum sibiricum polysaccharides could attenuate the damage from diabetic retinopathy, while dry eyes can be relieved by mucoadhesive Bletilla striata polysaccharide-based artificial tears ( Chandel et al, 2019 ; Wang et al, 2019c ; Thacker et al, 2020 ). Evidence has also demonstrated that phyto-based polysaccharides can be utilized for drug delivery systems upon graft modification or synergistic interaction via non-covalent stabilization with other commercial polysaccharides such as hyaluronic acid ( Uccello-Barretta et al, 2013 ; Wang et al, 2019b ).…”
Section: Bioactive Polysaccharide-based Nanocarriers For Ocular Delivmentioning
confidence: 99%
“…P. sibiricum is a well-known traditional medicinal herb in China ( 15 ), as well as a health-improving substance ( 16 ). P. sibiricum has been widely used in a number of Chinese herbal medicine compounds treating different diseases as recorded in Ben Cao Gang Mu ( Compendium of Materia Medica ) and its effects in treating diabetes ( 17 ), cardiovascular and cerebrovascular diseasess18), somnipathy ( 19 ), dyslipidemia and pathological fatigue ( 20 ) have also been determined by modern medical methods.…”
Section: Introductionmentioning
confidence: 99%